A Modified Leach Algorithm Using Hard and Soft Threshold in Wireless Sensor Network: A Review - Kaur, Gurpreet; Arora, Vishal (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Wireless sensor networks have become increasingly popular due to their wide range of application. Clustering sensor nodes organizing them hierarchically have proven to be an effective method to provide better data aggregation and scalability for the sensor network while conserving limited energy. Minimizing the energy consumption of a wireless sensor network application is crucial for effective realization of the intended application in terms of cost, lifetime, and functionality. However, the minimizing task is hardly possible as no overall energy cost function is available for optimization. In this paper, we have proposed a modified alogirthm of leach where hard and soft threshold values will be applied for improving the overall throughput and network lifetime.